Razmerja v izbrani sodobni slovenski kratki prozi - Žbogar, Alenka (Jezik in slovstvo, 2020)
The article highlights family and partner relationships in selected contemporary Slovenian short story collections published in the first decade of the twenty-first century. The following collections are analysed: Law of Desire (2000) by Andrej Blatnik, Made in Slovenia (2007) by Aleš Čar, All My Christmas (2006) by Maruša Krese, Guerrilla (2004) by Polona Glavan and Fragma (2003) by Mojca Kumerdej. We attempt to clarify the kind of family and partner dynamics reflected in these collections, and consider whether the selected collections fall within so-called literary minimalism and in which areas this is reflected. We explain why subjects of conversation dominate in these collections and the extent to which they fit the Iceberg Theory.
Keywords: 2000-2010; Blatnik, Andrej; comparative analyses; Čar, Aleš; družinska razmerja; family relationships; Glavan, Polona; Iceberg Theory; Krese, Maruša; Kumerdej, Mojca; literarne študije; literarni minimalizem; literary minimalism; literary studies; partner relationships; partnerska razmerja; primerjalne analize; Slovenian literature; Slovenian short stories; slovenska književnost; slovenska kratka proza; subject of conversation; subjekt pogovarjanja; teorija ledene gore